International development navigating humanity's greatest challenge - Woolcock, Michael 1964- (polity, 2023)
Whether understood as a long-run historical process or an intentional political project, international development transforms not only societies and economies but also key ideas about how the world works and how problems should be solved. At its best, development yields enormous benefits for human welfare, yet actually realizing and securing them is perhaps humanity's greatest challenge.In this compelling book, Michael Woolcock - Lead Social Scientist at the World Bank - demonstrates that achieving peace and prosperity for all is supremely contingent and often contentious: the means and ends of development are often perceived as alien, unjust, and disruptive, its benefits and costs unequally borne. Many development challenges are not technical problems amenable to an expert's solution, requiring instead extensive deliberation to find and fit context-specific responses. Flailing attempts to ""build the rule of law"" - perhaps the only development goal shared across the political spectrum in the global North and South - embody this central conundrum. Woolcock insists that it is each generation's challenge to find shared, legitimate, and durable solutions to the moral imperative to reduce human suffering while simultaneously redressing the vexing challenges that development success (let alone failure) inexorably brings.This skillful guide will be essential reading for students and practitioners working in this complex field, and for anyone seeking to help 'make the world a better place'
Keywords: Entwicklungspolitik; Entwicklungstheorie; Entwicklungstheorie, Entwicklungspolitik